2022
DOI: 10.1111/lam.13658
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of genes encoding carbapenemase, ESBL, pAmpC and non-β-Lactam resistance among Klebsiella pneumonia and E. coli clinical isolates in Tunisia

Abstract: This study aimed to investigate the molecular mechanisms of carbapenem and colistin resistance in K. pneumoniae and E. coli isolates obtained from hospitalized patients in Carthagene International Hospital of Tunis. A total of 25 K. pneumoniae and 2 E. coli clinical isolates with reduced susceptibility to carbapenems were recovered. Susceptibility testing and phenotypic screening tests were carried out. ESBL, AmpC, carbapenemase and other antibiotic resistance genes were sought by PCR‐sequencing. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Interestingly, K. pneumoniae ST101 is one of the major high-risk clonal lineages of carbapanemase-producing isolates highly associated with hospital-acquired infections worldwide (David et al 2019). In Tunisia, the ST101 was recently reported in CTX-M-15and OXA-48-producing K. pneumoniae in hospital settings and communities (Mansour et al 2015;Ben Tanfous et al 2017Ben Sallem et al 2022). Similarly, carbapenemase-producing K. pneumoniae ST13 and ST37 clones have been reported as prevalent clones in various geographic regions, such as Portugal (Mendes et al 2022), Brazil (Rodrigues et al 2022) and Italy (Di Pilato et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, K. pneumoniae ST101 is one of the major high-risk clonal lineages of carbapanemase-producing isolates highly associated with hospital-acquired infections worldwide (David et al 2019). In Tunisia, the ST101 was recently reported in CTX-M-15and OXA-48-producing K. pneumoniae in hospital settings and communities (Mansour et al 2015;Ben Tanfous et al 2017Ben Sallem et al 2022). Similarly, carbapenemase-producing K. pneumoniae ST13 and ST37 clones have been reported as prevalent clones in various geographic regions, such as Portugal (Mendes et al 2022), Brazil (Rodrigues et al 2022) and Italy (Di Pilato et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…2017, 2018; Ben Sallem et al . 2022). Similarly, carbapenemase‐producing K. pneumoniae ST13 and ST37 clones have been reported as prevalent clones in various geographic regions, such as Portugal (Mendes et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the African continent, besides South Africa, ST307 was found to be predominant among ESBL-producing K. pneumoniae isolated between 2016 and 2018 from three sentinel surveillance hospitals in Nigeria [ 22 ]. In addition, a K. pneumoniae ST307 clinical isolate harboring the bla OXA-48 gene on an IncL-type plasmid was reported in Tunisia in the same period [ 23 ]. Of note, genome sequencing identified ST307 among chimpanzees and termites in protected areas in Senegal, suggesting the circulation of strains between the two species [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the isolates were resistant to the newly developed ceftazidime/avibactam combination. pneumoniae ST307 clinical isolate harboring the blaOXA-48 gene on an IncL-type plasmid was reported in Tunisia in the same period [23]. Of note, genome sequencing identified ST307 among chimpanzees and termites in protected areas in Senegal, suggesting the circulation of strains between the two species [24].…”
Section: Antimicrobial Resistancementioning
confidence: 92%
“…In Tunisia, Sallem et al showed wide variation in the distribution of ESBLs, AmpC, carbapenemase and other plasmid-mediated resistance determinants. Isolates of Klebsiella pneumoniae producing carbapenemase activity carried variants of the blaNDM-1 (n = 11), blaOXA-48 (n = 11), blaNDM-1 + blaOXA-48 (n = 1), blaNDM-1 + blaVIM-1 (n = 1), blaOXA-204 (n = 1), as well as variants of the blaCTX-M, blaOXA, bla-TEM, blaCMY, blaDHA and blaSHV genes on conjugative plasmid [30]. This could be explained by the fact that, Klebsiella easily host carbapenemases genes.…”
Section: Discussionmentioning
confidence: 99%